The association between family relationships and depressive symptoms among pregnant women: A network analysis - Wang, Jingjing; Pei, Yifei; Tang, Jie; Chen, Qian; He, Chenlu; Zhang, Ying; Hou, Hao; Zhang, Xunbao; Wang, Wei (Frontiers in Psychiatry, 2022)
Abstract Background: Depression of pregnant women has been a growing concern in recent years, and previous research has found that family relationships are strongly associated with depression. From a network perspective, family relationships and depression can be conceptualized as the result of interactions between individual symptoms. This research approach can elucidate the structure and mechanisms of the relationship between individual symptoms within the two groups. Methods:A total of 990 participants were recruited from the obstetrics outpatient clinic of Maternal and Child Health Hospital in Huai’an through a randomized whole-group sampling. Respondents’ depressive symptoms and family relationships were self-reported using questionnaire, and the structure of the family relationship-depressive symptoms network and related centrality indicators were examined for this sample. Results: The results of the network analysis suggested that the most influential symptoms in the network of family relationship-depressive symptoms were worry, feeling worthless, equal status with husband and couple relationship. And equal status with husband was the most prominent bridging symptoms in this study. The whole network was robust in both stability and accuracy tests. Limitations: Information was obtained from subjects' self-reports, which may be subject to information bias. As a cross-sectional study, no causal link between family relationships and depressive symptoms can be established. Conclusion: Worry, feeling worthless, equal status with husband and couple relationship are central symptoms of the family relationship-depressive symptoms network structure in pregnant women. Timely and systematic multilevel interventions targeting the central symptoms may be effective in alleviating the onset of depressive symptoms in women during this period.